Steven Baur, Raymond Knapp and Jacqueline Warwick (eds), Musicological Identities: Essays in Honor of Susan McClary (2008) - Morris, Christopher (Journal of the Society for Musicology in Ireland, 2009)
A review of Steven Baur, Raymond Knapp and Jacqueline Warwick (eds), Musicological Identities: Essays in Honor of Susan McClary (Aldershot and Burlington, VT: Ashgate, 2008), ISBN 978-0-7546-6302-7